Subjective and objective performance of the Lenstec KH-3500 "accommodative" intraocular lens. Issue 6 (10th March 2006) - Wolffsohn, J S; Naroo, S A; Motwani, N K; Shah, S; Hunt, O A; Mantry, S; Sira, M; Cunliffe, I A; Benson, M T
Abstract : Aim: To determine whether eyes implanted with the Lenstec KH-3500 "accommodative" intraocular lenses (IOLs) have improved subjective and objective focusing performance compared to a standard monofocal IOLs. Methods: 28 participants were implanted monocularly with a KH-3500 "accommodative" IOL and 20 controls with a Softec1 IOL. Outcome measures of refraction, visual acuity, subjective amplitude of accommodation, objective accommodative stimulus response curve, aberrometry, and Scheimpflug imaging were taken at ∼3 weeks and repeated after 6 months. Results: Best corrected acuity with the KH-3500 was 0.06 (SD 0.13) logMAR at distance and 0.58 (0.20) logMAR at near. Accommodation was 0.39 (0.53) D measured objectively and 3.1 (1.6) D subjectively. Higher order aberrations were 0.87 (0.85) μm and lower order were 0.24 (0.39) μm. Posterior subcapsular light scatter was 0.95% (1.37%) greater than IOL clarity. In comparison, all control group measures were similar except objective (0.17 (0.13) D; p = 0.032) and subjective (2.0 (0.9) D; p = 0.009) amplitude of accommodation. Six months following surgery, posterior subcapsular scatter had increased (p<0.01) in the KH-3500 implanted subjects and near word acuity had decreased (p<0.05). Conclusions: The objective accommodating effects of the KH-3500 IOL appear to be limited, although the subjective and objective accommodative range is significantly increased compared to control subjects implanted with conventional IOLs. However, this "accommodative" ability of the lens appears to have decreased by 6 months post-surgery.